Perancangan Dan Implementasi Sistem Informasi Pemasaran Digital Pada UMKM Madu Zalfa Berbasis Web - Ami Wulandari, Cinthia; Dodo Zaenal Abidin; Joni Devitra (LPPM Universitas Dinamika Bangsa, 2025)
The rapid development of digital technology, particularly the internet, has significantly impacted marketing activities. Many small and medium-sized enterprises (SMEs), such as Toko Madu Zalfa, still rely on traditional marketing methods, which are less effective in reaching a broader market. This study aims to design and implement a web-based digital marketing information system for Toko Madu Zalfa to improve marketing efficiency and expand customer reach. This research utilizes the Waterfall method, consisting of system analysis, design, implementation, and testing phases. The information system is designed using the PHP programming language and MySQL database, supported by UML (Unified Modeling Language) modeling tools to outline the system's flow. The system allows admins to manage product information, outlets, and customer testimonials digitally while providing reports related to products and promotions. Additionally, customers can easily access product information through the website without needing to visit the store in person, accelerating the marketing process and reducing promotional costs. The implementation results demonstrate that this information system successfully increases Toko Madu Zalfa's marketing reach and operational efficiency, while facilitating integrated data management. Therefore, this system is expected to assist Toko Madu Zalfa in competing in the digital era and expanding its market beyond the province.